The Application of Article 359 of the Criminal Code In the Investigation of the Death of Post-Operative Patients (Juridical Analysis: Case of the Death of Three Patients in the MHP Hospital, Lampung) - I Ketut Seregig (Faculty of Law, Sriwijaya University, Indonesia, 2017)
The incident of the death of three post-operative patients in a line at the MHP hospital, Lampung on April 5, 2016 had emerged the decline of public confidence toward hospitals, both public and private hospitals. The symptoms in the patients’ body before they died were convulsed and decreased consciousness. Based on dr. AA, Sp.An., if post-operative impact occurs, then a person who takes responsibility is an anesthesiologist. This means that responsible for the death of these patients was the doctor who performed anesthesia before the operation. All three patients, who died after operation in MHP Hospital, respectively, were Mr. RM suffered from varicose; Mr. S the patient with a tumor in the left leg calf; and Mrs. DP who performed a caesarean section. These patients underwent a convulsion and decreased consciousness after operation, although the anesthesiologist had tried to save their life. Yet, these patients died. During the operation, the doctor had operated with the use of Standard Operating Procedures. Based on the information from the Chairman of IDI and the Chairman of MKEK, they said that dr. EP, Sp. An. As the anesthesiologist had done the right procedures in doing anesthetic injection to these patients. During the investigation process conducted by the Regional Police of Lampung, toward dr. EP, Sp. An., he was presupposed in violation of Article 359 of the KUHP which stated